Application of Dzyadyk’s polynomial kernels in the constructive function theory - Andrievskii, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
This is a survey of recent results in the constructive theory of functions of complex variable obtained by the author through the application of the theory of Dzjadyk’s kernels combined with the methods and results from modern geometric function theory and the theory of quasiconformal mappings.